2008 4th International Conference on Ultrawideband and Ultrashort Impulse Signals 2008
DOI: 10.1109/uwbus.2008.4669404
|View full text |Cite
|
Sign up to set email alerts
|

Dual regularization in inverse problem of low frequency dielectric profiling

Abstract: The new approach of dual regularization is applied to the problem of geomagnetic low frequency profiling of conductivity of earth crust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Results of the numerical study in the problem of low-frequency sounding of the Earth crust [3] have demonstrated serious limitations of such approach for large perturbations, when the Born approximation (first guess of iterative method) is inapplicable. To overcome these restrictions of perturbation theory, the new method of dual regularization based on the Lagrange approach in the optimization theory [4] has been applied [5] in this problem. Results show its ability to retrieve very strong variations of conductivity profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the numerical study in the problem of low-frequency sounding of the Earth crust [3] have demonstrated serious limitations of such approach for large perturbations, when the Born approximation (first guess of iterative method) is inapplicable. To overcome these restrictions of perturbation theory, the new method of dual regularization based on the Lagrange approach in the optimization theory [4] has been applied [5] in this problem. Results show its ability to retrieve very strong variations of conductivity profiles.…”
Section: Introductionmentioning
confidence: 99%